Urban Food Crop Farming and Farm Households’ Food Security Status in Oyo State, Nigeria - Olaleye, David Tobi; Obayelu, Abiodun Elijah; Ogunmola, Omotoso Oluseye (Applied Studies in Agribusiness and Commerce, 2018)
Food production and supply has been on the decline in Nigeria with a consequent impact on household food security. This study examined the influence of urban farming on household food security in Oyo State, Nigeria. Multi-stage sampling procedure was used to select 159 farm households in a cross-sectional survey. Structured questionnaire was used to obtain data on socio-economic characteristics, determine the food security status of urban crop farming households in the study area, and examine the effects of urban crop production on households’ food security status. Data were analysed using descriptive statistics while the statistical tools were Food Security Index (FSI) and Probit Regression Model (PRM). Results revealed that 84.9% of the respondents was male, 81.2% married. The average age, household size, and farm size were 49.6 years, 6 persons, 1.1 hectares respectively. Most (75.5%) of the respondents did not have access to consumption credit and 62.3% did not belong to any farmers association. Based on minimum daily energy requirement per adult equivalent of N230.8, 90.6% of the farm households was food secure.The PRM showed that age (β = -0.1, p